Quantifying potential carbon dioxide removal via enhanced weathering using porewater from a field trial in Scotland - McBride, Amy L.; Skov, Kirstine; Wade, Peter; Betz, Joey; Stubbs, Amanda; Bierowiec, Tzara; Albahri, Talal; Cazzagon, Giulia; Chen, Chieh-Jhen; Frew, Amy; Healey, Matthew; Idam, Ifeoma; et al. (Frontiers in Climate, 2025)
Enhanced weathering (EW) is cited as a promising carbon dioxide removal (CDR) strategy, and is being rapidly commercialized. Rigorous monitoring, reporting and verification (MRV) are essential to ensure carbon claims are accurate and carbon credits are not mis-sold. MRV protocols incorporate multiple approaches, including soil and porewater sampling. This paper calculates potential CDR (pCDR) from porewater (direct pCDR), via an alkalinity estimation calculated from charge balance, and from soil samples (inferred pCDR), via the accumulation of exchangeable cations on soil exchange sites. These pCDR estimations are then compared to the maximum theoretical CDR potential. The data were collected from a 1.5 year field trial, situated in south-east Scotland. Crushed basalt was surface-applied to plots at rates of 0 (control), 23, 78 and 126 t ha−1. Application rates were increased relative to common agricultural spreading practices (78 and 126 t ha−1) to increase the chances of detecting a signal. To calculate direct pCDR from porewater, ion concentrations of porewater samples extracted from a depth of 5 and 10 cm were integrated with precipitation surplus to estimate the flux of cations leaching from each depth over c. 2 week periods, as water budgets allowed. Ordinary least squares model results identified a significant effect of treatment as an explanatory variable for potential CDR, both at 5 and 10 cm depth. Direct pCDR ranging from 0.33 to 0.53 tCO2 ha−1 after c. 1.5 years of weathering was calculated in the 5 cm depth treatment in the 78 and 126 t ha−1 application treatment relative to the control. The model prediction interval was overlapping between the control and the 23 t ha−1 treatment at 5 cm depth, as well as for all the treatments in the 10 cm treatments when evaluated relative to the control. Carbonate precipitation was also assessed, but remained below the detection limit (0.1 wt.% inorganic carbon). Inferred pCDR calculated from 30 cm-deep soil samples were not significant, possibly as a result of experimental design and sampling density. Overall, when direct pCDR is normalized to mass of rock applied and duration of weathering (e.g., mass-time-normalized-pCDR), the values fall within the mid-range of values published from other field studies.